A Methylome‐Wide Association Study of Trajectories of Oppositional Defiant Behaviors and Biological Overlap With Attention Deficit Hyperactivity Disorder. Issue 5 (20th September 2017) - Barker, Edward D.; Walton, Esther; Cecil, Charlotte A.M.; Rowe, Richard; Jaffee, Sara R.; Maughan, Barbara; O'Connor, Thomas G.; Stringaris, Argyris; Meehan, Alan J.; McArdle, Wendy; Relton, Caroline L.; Gaunt, Tom R.
Abstract : In 671 mother–child (49% male) pairs from an epidemiological birth cohort, we investigated (a) prospective associations between DNA methylation (at birth) and trajectories (ages 7–13) of oppositional defiant disorder (ODD), and the ODD subdimensions of irritable and headstrong; (b) common biological pathways, indexed by DNA methylation, between ODD trajectories and attention deficit hyperactivity disorder (ADHD); (c) genetic influence on DNA methylation; and (d) prenatal risk exposure associations. Methylome‐wide significant associations were identified for the ODD and headstrong, but not for irritable. Overlap analysis indicated biological correlates between ODD, headstrong, and ADHD. DNA methylation in ODD and headstrong was (to a degree) genetically influenced. DNA methylation associated with prenatal risk exposures of maternal anxiety (headstrong) and cigarette smoking (ODD and headstrong).